Psalmist's cry scripts for embracing lament - Brueggemann, Walter; Frost, Steve ([Kansas City, Mo.] : House Studio, 2010)
"In Psalmist's Cry, Walter Brueggemann explores Psalms as scripts for lament-guides for how to express feelings honestly, in ways normally not permitted or expected within the Christian community. In this 5-week study, discover the fullness of God when we allow our lives to become about him healing us and not about us controlling or managing our way through life." -- from book cover.
Description based on print version record.
Keywords: Bible. -- Commentaries; Bible. -- Study and teaching; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Electronic books